Serotonin syndrome induced by the readministration of escitalopram after a short-term interruption in an elderly woman with depression: a case report - Sato Y (Dove Medical Press, 2015)
Yasushi Sato,1,2 Kazuhiko Nakamura,1 Norio Yasui-Furukori1 1Department of Neuropsychiatry, Graduate School of Medicine, Hirosaki University, Hirosaki, Japan; 2Department of Psychiatry, Tsugaru General Hospital, Goshogawara, Japan Background: Serotonin syndrome is a rare but potentially fatal side effect of antidepressants that results from the effects of drug activity on both central and peripheral serotonergic receptors. Case: A 78-year-old Japanese female with a 2-year history of major depressive disorder was treated with escitalopram (10 mg/d), risperidone (1 mg/d), and nitrazepam (5 mg/d). One month after beginning this drug regimen, she was transferred to the emergency department and immediately hospitalized due to suspicion of a urinary tract infection and dehydration. All psychotropic drugs were discontinued. Five days later, the patient’s physical condition had recovered; therefore, the same dose of escitalopram (10 mg/d) was readministered. The patient subsequently developed convulsions accompanied by impaired consciousness, high fever, and myoclonus of both upper extremities. The tendon reflexes of both lower extremities were enhanced. Based on these clinical signs and symptoms, we suspected serotonin syndrome; therefore, escitalopram was discontinued, and a fluid infusion was initiated. The patient recovered from all symptoms within 3 weeks without receiving additional antidepressants. Conclusion: This case suggests that the careless readministration of selective serotonin reuptake inhibitors (SSRIs) is harmful to at-risk patients, like those in poor physical condition and the elderly. Keywords: serotonin syndrome, escitalopram, readministration